Development of plug-in air powered four wheels motorcycle drivetrain control unit - Tan, Beng Leng (2013)
This thesis is related to the development of plug-in air powered four wheel motorcycles drive train system that transfers rotational energy from power train to the driving wheel. The objective of this thesis is to develop an air hybrid drivetrain unit and control the power and torque from the powertrain to the driving wheel by using sequential manual transmission. This thesis describes the process of developing sequential shift-by-wire system to make gear shifting for easier for 4 wheel motorcycle. The controller used in this project was 18F PIC 4550 microprocessor. The system programming performed using FLOWCODE version 4.0. 2 units of electromechanical linear actuator were used in this project as an actuator for gear shifting on a manual transmission. Chain drives were selected as power transfer linkage from air hybrid engine to the driving wheel with under drive configuration. Besides the development of shift-by-wire system, the torque on the driving wheel also had been calculated and analysed. In additional, the maximum speed that can be achieved by four wheel motorcycles was also calculated.